Philippine foreign trade profile 1989-90. - Philippines. Bureau of Export Trade Promotion (Makati, Metro Manila Bureau of Export Trade Promotion, Dept. of Trade & Industry, 1991)
Annual.
v.1. United States and the Americas.--v.2. European Economic Community.--v.3. Europe, other than EEC.--v.4. Japan and Oceania.--v.5. ASEAN and the rest of Asia.--v.6. The Middle East and Africa.
Title from cover.
Keywords: Philippines -- Commerce; Commercial statistics